Evidence-based Reviews in Surgery Long-term Outcome of Surgery Versus Conservative Management for Recurrent and Ongoing Complaints After an Episode of Diverticulitis: Five-year Follow-up Results of a Multicenter Randomized Controlled Trial (DIRECT-Trial). Issue 2 (August 2020) - Patel, Sunil V.; Hendren, Samantha; Zaborowski, Alexandra; Winter, Des
Abstract : Question: Does surgery or conservative management of recurring diverticulitis/ongoing symptoms results in a higher quality of life (QoL) at 5-year follow-up. Design: Randomized controlled trial. Setting: Multicenter trial in the Netherlands. Patients: Patients aged 18 to 75 years, who presented with either ongoing abdominal complaints (for >3 months) and/or frequently recurring left-sided diverticulitis (>2 episodes in 2 years) after an objectified (via Computed Tomography, Ultrasound or Endoscopy) episode of diverticulitis were included in this study. Intervention: Elective Sigmoid Resection within 6 weeks vs. Conservative Management Main Outcome: QoL at 5-year follow-up, as measured by the Gastrointestinal Quality of Life Index (GIQLI). Secondary outcomes included additional QoL assessments (including the EuroQoL-5D-3L, Visual Analogue Score for pain, and the short form 36 health survey) Results: The intention to treat analysis showed the surgical group had a higher quality of life (GIQLI) score than the conservative group (mean difference 9.7, 95% confidence interval 1.7–17.7, P = 0.018), which approached but did not meet the minimum important difference of 10. This difference was achieved in 67% of those in the operative group versus 57% in the conservative group (many of who eventually underwent surgery). Conclusions: The study results demonstrate that HRQOL at 5-year follow-up may be improved in patients undergoing surgical resection, although this difference did not meet the MID for the GIQLI.